POBREZA E TERRITÓRIOS (DE POBREZA): configurações a partir da Política de Assistência Social - Maria do Socorro Sousa de Araújo (Universidade Federal do Maranhão, 2018)
The article approaches reflections developed on Social Assistance as Public Policy inserted on the Tripod of Social Security in Brazil and in the extension of social rights. It discusses the criteria for defining social groups as a priority target audience, based on the configuration of poverty territories; problematizes the criteria used for the adoption of the territorialization of the Social Assistance Policy, taking into account the Brazilian ethnic, social and territorial diversity.